Impact of economic factors on profitability: evidence from listed manufacturing companies in sri lanka - Anushiya, A.; Vani, S. (University of Jaffna, 2016)
The aim of this study is to examine the impact of Economic Factors on Profitability in Listed manufacturing companies. Profitability plays an important role in the structure and development of firm. It also enhances the reputation of a firm. Firm's profitability is dependent of the various factors like firm's capital structure, board size, political factors, economical factors and global environmental changes etc. The purpose of the study is to investigate, empirically, the relationship between the profitability and the economic factors and its impact on profitability. Firm profitability is dependent upon micro-economic factors and macro-economic factors. In this respect, the study has been conducted using data drawn for 2011 to 2015 from listed manufacturing sector in Sri Lanka, since the sample size in this study constitute the 15 companies by randomly selected among the 38 listed manufacturing companies. Secondary data were collected from annual financial report of selected companies, in order to answer the research questions. The various variables were used to measure the impact of economic factors on Profitability. Such as, Liquidity ratio, Debt ratio, and Average inflation rate as independent proxies whereas Return on asset (ROA) is considered as dependent proxies. The researchers use the Pearson's correlation analysis and regression models to investigate the said relationships. Results of the main analysis show that economic factors have very little role on firm profitability in manufacturing companies in Sri Lanka. The results from the present study may be very encouraging and useful for managers as well as investors to plan investment and operational activities to achieve profitability objectives more efficiently and effectively.
Keywords: Inflation rate; Manufacturing companies; Microeconomic factors; Profitability